PERUBAHAN POTENSI MENGEMBANG TANAH EKSPANSIF YANG DISTABILISASI SECARA FISIS DAN MEKANIS - Paksitya Purnama Putra; Mokhammad Farid Ma'ruf; Muhammad Ari Ridwansyah; Rendra Kurniawan; Celia Nindy Carisa (Politeknik Negeri Jakarta, 2021)
Expansive soil has a high swelling and shrinkage ability which can damage the buildings above it. Glagahagung Village, Purwoharjo District, Banyuwangi Regency is one of the areas suspected of having this type of soil. Residents often experience problems in their residential buildings every year, such as cracks in floors, walls, columns, and beams. Several methods can be used to improve expansive soil, including physical and mechanical stabilization. In this study, lime and cement were used as physical stabilizers. On the other hand, sand is used as a mechanical stabilizer. Physical and mechanical parameters will be observed in the stabilization process. Based on the three stabilizers, a 5% cement mixture can be the best alternative. Cement stabilizers can increase the maximum dry volume weight, reduce the rate of soil swelling, and change natural soils' classification from high plasticity clay to silty sand. Keywords: Expansive Soil, Mechanical Stabilization, Physical Stabilization, Swelling Potential.